Rescate del conocimiento ancestral medicinal en la comunidad de Piava, cantón Cotacachi - Gonzalez Andrade, Tamia Elena (2023)
Ecuador stands out for its cultural diversity and broad cultural heritage of peoples and nationalities. In Cotacachi, mystical tourism is an opportunity for the rescue of ancestral medicinal knowledge, standing out for treating physical and supernatural ailments, generating the interest of tourists in the practice of ancestral medicine. Mystical tourism plays a fundamental role in the promotion of cultural wealth and in encouraging the search for physical, mental and spiritual wellbeing, being a beneficial activity for practitioners and tourists. The general objective of the study is to revalue the knowledge of ancestral medicine of the community of Piava, through tourism diversification to promote the practice of the modality of mystical tourism. A mixed approach was developed implementing analytical, synthetic and deductive methods. In addition\; the techniques were documentary, surveys, interviews and observation. The study universe was 40,036 inhabitants of the Cotacachi canton, and after applying the calculation, a sample of 165 surveys was obtained. The results determined the interest in ancestral medicine as a tourist product. With respect to the field work, six observation sheets were developed\; 3 about the plants used in ancestral practices, 2 about the sacred sites located in the community of Piava and finally an ethnobotanical garden. Based on the research conducted, the creation of a tourist route including sacred sites and ancestral medicine practices is proposed. It is concluded that mystical tourism seeks deep spiritual experiences guided by yachaks and healers, likewise ancestral medicine offers an opportunity to develop this type of tourism and attract visitors interested in authentic and spiritual experiences, which they will find by participating in the Ally Kawsay route.